Femoral fracture in the elderly: dependence on nursing care - Augusto Baisch de Souza; Daniela Tonroller de Oliveira; Sidiclei Machado Carvalho; Jonas Michel Wolf; Tiago Claro Maurer; Lucas Henrique Rosso (Universidad de Santander, 2023)
Introduction: Due to the aging of the population, nursing processes have been adapted to these patients, who require a high level of care and guidance. Objective: Analyzing the degree of dependence on nursing care by elderly patients (65 years or older) with femur fractures. Materials and Methods: retrospective, with a quantitative approach, carried out in a private hospital from April 2021 to April 2022. The sample comprehends 41 patients, analyzed epidemiological data and degree of dependence Study of nursing care during hospitalization, environment of hospitalization and discharge, according to the SCP. Results: Composed of 41 patients, mean age of 84 years and female predominance (75.61%). With regard to fractures, there was a greater occurrence due to falls from standing height and predominance of neck fractures, with an average time until surgery of less than 16 hours. Systemic Arterial Hypertension and Diabetes Mellitus were predominant. The average of the SCP estimates presented 24.26 in the 1st, 26.12 in the 2nd and 26.24 in the 3rd. The length of hospital stay was 7 days and no deaths were reported. Discussion: The findings on sociodemographic data, reasons for falls, location, comorbidities, degree of dependence and length of hospital stay are similar to those available in databases. They differ, in better quality, under time until surgery and clinical. Conclusions: The study presents specific knowledge to carry out the care of the intra-hospital nursing process, thus allowing the systematization of the team's assistance.